2017
DOI: 10.1111/hsc.12417
|View full text |Cite
|
Sign up to set email alerts
|

An extra care community's perceived priorities for ‘whole system’ relationships: a Q-methodological study

Abstract: Health and social care settings worldwide need to sustainably improve the quality of relationships across communities or 'whole systems'. This research informs the development of a relational framework based on stakeholder perspectives. It is grounded in an action research project with practitioners, and draws on a previous literature review, to present the underpinning elements of quality relationships as statements, organised under the headings of integrity, respect, fairness, compassion and trust. Using Q m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Q-methodological studies in healthcare included a diverse range of stakeholders (e.g., patients, doctors, nurses, informal caregivers, medical students), which could be broadly classified as those receiving or consuming care (consumers) or those delivering or organising formal care (providers). Thirty studies (10.4%) [ 27 , 53 , 59 , 64 , 81 106 ] involved both consumer and provider participants. Four of these studies [ 87 , 92 , 105 , 107 ] did not clearly report the breakdown between the types of participants.…”
Section: Resultsmentioning
confidence: 99%
“…Q-methodological studies in healthcare included a diverse range of stakeholders (e.g., patients, doctors, nurses, informal caregivers, medical students), which could be broadly classified as those receiving or consuming care (consumers) or those delivering or organising formal care (providers). Thirty studies (10.4%) [ 27 , 53 , 59 , 64 , 81 106 ] involved both consumer and provider participants. Four of these studies [ 87 , 92 , 105 , 107 ] did not clearly report the breakdown between the types of participants.…”
Section: Resultsmentioning
confidence: 99%
“…The wider policy implications of the value of ECH hinge upon its part in an integrated system of care. This is noted in a study which showed that ECH could act as a "powerful and effective resource" (Grimshaw et al, 2017(Grimshaw et al, , p. 1169).…”
Section: Implications For Practice and Researchmentioning
confidence: 90%
“…However, the framework or means to ensure that the concourse is fully representative of the opinions available on the topic is rarely articulated. Articles selected were published between 1996 (Brown 1996) and 2017 (Dune et al, 2017;Grimshaw et al 2017). Generally, the type of concourse data identified are articulated as textual statements.…”
Section: Analysis and Interpretation Of Datamentioning
confidence: 99%